Percutaneous Transhepatic Biliary Drainage Complicated by Bilothorax - Kim, Stephanie H.; Zangan, Steven M. (Seminars in Interventional Radiology, 2015)
Percutaneous transhepatic biliary drainage (PTBD) is a well-established and safe technique for the management of biliary obstructions and leaks. While approach is variable based on operator preference, patient anatomy, and indications; PTBD is commonly performed via a right-sided intercostal route. With a right-sided approach, pleural complications may be encountered. The authors describe a case of a right PTBD complicated by a leak into the pleural space, with the subsequent development of bilothorax.
Keywords: transhepatic biliary drainage; bilothorax; pleural; complication; interventional radiology